Self-efficacy instruments for individuals with coronary artery disease: a systematic review protocol - Karolinne Souza Monteiro; Jose Alexandre Barbosa Almeida; Rêncio Bento Florêncio; Darllane Azevedo Lemos; Jéssica Costa Leite; Lucien Peroni Gualdi (BMJ Open)
Introduction Self-efficacy is associated with management of diseases, psychological well-being, improved quality of life and rehabilitation adherence. Several instruments related to behaviour or specific disease (eg, coronary artery disease (CAD)) assess self-efficacy. The evaluation of cardiac self-efficacy in individuals with CAD will support healthcare professionals to improve self-efficacy via interventions; therefore, a suitable instrument is crucial. This systematic review aims to assess measurement properties, methodological quality and content of outcome measures of cardiac self-efficacy instruments for individuals with CAD.Methods and analysis The study has been developed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol and Consensus Norms for Selection of Health Measuring Instruments (COSMIN). The following databases will be searched: MEDLINE (Ovid), Web of Science, EMBASE and PsycINFO. Studies assessing measurement properties of cardiac self-efficacy instruments for individuals with CAD will be included. No date or language restrictions will be applied to the search. Two independent authors will be responsible for assessing the eligibility of studies. Methodological quality of studies will be assessed using the COSMIN RoB Checklist, and the Grading of Recommendations, Assessment, Development and Assessment will be used to assess the quality of each study. Two authors will independently evaluate the content of instruments and link this to the International Classification of Functioning, Disability and Health.Ethics and dissemination This study does not require ethics committee approval since it is based on previously published data. Evidence from this systematic review will be disseminated through publication in peer-reviewed journals and presentation at scientific conferences.PROSPERO registration number CRD42021262613.